Methodology to Estimate the Financial Impacts of the Integration of PV Generators in Distribution Systems on Voltage Sags and Energy Losses - Cebrian, Juan C. [UNESP]; Giacomini, Jairo [UNESP]; Rossi, Andre L. D. [UNESP]; Trindade, Fernanda C. L.; Paredes, Helmo K. Morales [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2024)
In this paper, a methodology is proposed to, on the one hand, estimate gains on electric utilities with the minimization of annual financial losses due to voltage sags (FLsag) and cost of energy losses (SEL) as a result of financial investments on photovoltaic systems (CPVS) and, on the other hand, identify subsidies that can be offered by utilities to the end users aiming to cover part of the initial CPVS. The gains and subsidies are estimated by the identification of ideal locations and sizing of PVS, which considers the global minimization of CPVS, FLsag, and SEL. The methodology is applied to a real distribution network with 670 busbars. The results show that it is possible to achieve gains of 3.9% in FLsag and 25% in SEL and to offer subsidies to low-voltage PV owners between 14.5% and 16.5% of total CPVS to achieve strategic benefits for both electric utilities and end users. The identified gains and subsidies aim to offer fair tariffs to end users and to complement other economic incentives already offered by the government to increase the penetration rate of renewable energies.
Keywords: Electrical energy losses; photovoltaic systems; sensitive customers; subsidies; voltage sags